The association of growth and maturation with injury in academy soccer players: a narrative review - Hall, E. C. R.; Erskine, R. M. (Sports Medicine, 2026)
Background: The point of fastest growth during somatic maturation is termed `peak height velocity` (PHV), and the chronological age at which this occurs varies considerably. Academy football (soccer) players are typically categorised by chronological age, yet many children of the same age will naturally mature and grow at different ages and rates, respectively, which could affect injury risk. However, despite nearly two decades of studies investigating the association of growth and maturation with injury in academy footballers, confusion remains. Objective: To critically appraise the literature concerning the association of maturity timing, maturity status and growth rate with injury in academy football. Methods: Scopus, PubMed, SPORTDiscus and CINAHL databases were screened from inception until April 2025. Study design, setting, sample size, methods for estimating maturity timing/maturity status/growth rate, and injury reporting were evaluated in this narrative review to determine individual study quality. Results: A total of 472 articles were screened with data extracted from 26 eligible studies published between 2007 and 2025. Conclusions: We found that (i) early maturing players suffer more soft-tissue injuries than on-time or late maturing players; (ii) more growth-related injuries occur circa-PHV than pre- or post-PHV, but post-PHV players generally have greater injury risk than circa- or pre-PHV; and (iii) fast growth (stature increase = 7.2 cm per year) increases injury risk in academy footballers. However, all eligible studies demonstrated inherent limitations and none investigated the impact of maturity timing, maturity status or growth rate on injury in female academy players, indicating future research should address these issues.